2021
DOI: 10.1002/cmdc.202000952
|View full text |Cite
|
Sign up to set email alerts
|

Pentafluoro‐3‐hydroxy‐pent‐2‐en‐1‐ones Potently Inhibit FNT‐Type Lactate Transporters from all Five Human‐Pathogenic Plasmodium Species

Abstract: The protozoan parasite Plasmodium falciparum causes the most severe and prevailing form of malaria in sub-Saharan Africa. Previously, we identified the plasmodial lactate transporter, PfFNT, a member of the microbial formate-nitrite transporter family, as a novel antimalarial drug target. With the pentafluoro-3-hydroxy-pent-2-en-1-ones, we discovered PfFNT inhibitors that potently kill P. falciparum parasites in vitro. Four additional human-pathogenic Plasmodium species require attention, that is, P. vivax, mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…We circumvented the PfFNT G107S resistance by a strictly linear vinylogous acid-type compound with a nitrogen atom in the aromatic ring for hydrogen bonding with the serine-hydroxyl, i.e., BH267.meta (Figure 1) [12]. The compound further blocks FNT-type lactate transporters of the remaining four human-pathogenic plasmodia at sub-micromolar concentrations [13]. Sub-lethal doses of MMV007839 selected resistant parasites that carried a single PfFNT G107S point mutation shifting the MMV007839 efficacy by two orders of magnitude (IC 50 21 µM, EC 50 35 µM) [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We circumvented the PfFNT G107S resistance by a strictly linear vinylogous acid-type compound with a nitrogen atom in the aromatic ring for hydrogen bonding with the serine-hydroxyl, i.e., BH267.meta (Figure 1) [12]. The compound further blocks FNT-type lactate transporters of the remaining four human-pathogenic plasmodia at sub-micromolar concentrations [13]. Sub-lethal doses of MMV007839 selected resistant parasites that carried a single PfFNT G107S point mutation shifting the MMV007839 efficacy by two orders of magnitude (IC 50 21 µM, EC 50 35 µM) [4].…”
Section: Introductionmentioning
confidence: 99%
“…We circumvented the PfFNT G107S resistance by a strictly linear vinylogous acid-type compound with a nitrogen atom in the aromatic ring for hydrogen bonding with the serine-hydroxyl, i.e., BH267.meta ( Figure 1 ) [ 12 ]. The compound further blocks FNT-type lactate transporters of the remaining four human-pathogenic plasmodia at sub-micromolar concentrations [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…falciparum parasites, BH267.meta prevented the formation of drug resistance even when the parasite was treated with it for a long period [ 18 ]. Moreover, a recent study revealed that BH267.meta inhibits a broad spectrum of FNTs, including all causal agents of human malaria, indicating its potential application in further chemotherapeutic development [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…Sequence comparison of the FNT proteins from the five Plasmodium species that infect humans (P. falciparum, P. vivax, P. malariae, P. ovale, and P. knowlesi) showed > 84% overall similarity with the internal substrate transport path, with the isoforms being virtually identical [24]. The vital functionality and lack of similarity with the human MCTs appeared to be beneficial for the design of PfFNT-specific antimalarials.…”
Section: Introductionmentioning
confidence: 99%
“…Eventually, with BH267.meta, a compound was generated exhibiting nanomolar efficacy on the PfFNT wildtype and G107S mutant protein, as well as in 3D7 P. falciparum parasite in vitro cultures. Furthermore, BH267.meta showed very low cytotoxicity towards human cells [24] and minimal off-target potency on the human lactate transporter, MCT1 [24,37]. Cell viability as determined by ATP quantity and resazurin reduction and cell proliferation measured by nuclei count was tested using human kidney (HEK293) and liver (HepG2) cell lines.…”
Section: Circumvention Of the Pffnt G107s Resistance Mutation By Introduction Of Scaffold Nitrogen Atomsmentioning
confidence: 99%